Methods and applications of electrical conductivity enhancement of materials using carbon nanotubes - Abdulhameed, Abdullah; Abd Wahab, Nur Zuraihan; Mohtar, Mohd Nazim; Hamidon, Mohd Nizar; Shafie, Suhaidi; Abdul Halin, Izhal (Springer New York LLC, 2021)
Carbon nanotubes (CNTs) are used to enhance the electrical conductivity of electronic materials, due to their outstanding electrical properties. In this article, the general concept of CNT electrical conductivity and how it enhances the electrical conductivity of electronic materials is presented. The methods used to prepare and fabricate the enhanced materials are described, along with examples from selected work. We note that the CNT orientation and concentration within the enhanced material are the two main factors controlling the material electrical conductivity. Applications of each material are also reported so that the research efforts in material conductivity enhancement using CNTs are better appreciated. The applications of the enhanced materials range from consumer wearable electronics to precision biological electronic materials that can be inserted into the human body.